Effects of electric fields along different directions on the sensitivity and decomposition of TKX-50. (December 2022) - Hong, Dan; Zeng, Wei; Liu, Zheng-Tang; Liu, Fu-Sheng; Liu, Qi-Jun
Abstract: The sensitivity response of TKX-50 under electric fields along the [001], [010] and [100] directions was investigated using first-principles calculations. The discussions including structure, electronic properties, interaction of hydrogen bonds and covalent bonds all reflect the reduced stability of TKX-50 with increased electric fields. Moreover, these analyses also suggest that TKX-50 is the most sensitive when the electric field is applied in the [010] direction and TKX-50 likely has chemical decomposition and initiation at the value of 0.1/0.18 V/Å under the electric fields along the [010]/[100] directions. The systematic investigations of bond length, dissociation energies and the Hirshfeld population ratios of hydrogen bonds and covalent bonds reflect that TKX-50 is in a decomposition state under electric fields along the [010] and [100] directions due to hydrogen transfer. The gentle change of the above parameters indicates that TKX-50 may experience structural rearrangement under electric fields along the [001] direction, which can be attributed to efficient conversion of the energy acting on them into interlayer intermolecular interactions. Graphical abstract: Image 1 Highlights: The sensitivity response of TKX-50 under electric fields has been studied. TKX-50 is the most sensitive when the electric field is applied on [010] direction. TKX-50 may arise the structural rearrangement under the EEFs along [001] direction.